Możliwości zastosowania rachunku kosztów działań w działalności jednostek samorządu terytorialnego - Dylewski, Marek (Possibilities of Using Activity-Based Costing in Local Government Practice, 2007)
Process management needs the change of philosophy in spending public funds, first of all, it requires a construction of modern activity-based costing where classical costing form is not useful. Therefore, there is necessity to adopt accomplishments of management accounting. Standard budget statements are useless because they respond to a line item budget with a branch structure. A possibility of implementation of the new looking on local government activity is the main objective of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 130-137